The Role of Abnormal Placentation in Congenital Heart Disease; Cause, Correlate, or Consequence? - Courtney, Jennifer A.; Cnota, James F.; Jones, Helen N. (Frontiers in Physiology, 2018)
Congenital heart disease (CHD) is the most common birth defect, affecting approximately 1% of all live births. Despite improvements in clinical care, it is the leading cause of infant mortality related to birth defects and burdens survivors with significant morbidity. Yet after decades of research, the underlying cause of these defects remains unknown in the majority of cases. Population studies have recently demonstrated that pregnancies complicated by CHD also carry a higher risk of developing pathologies associated with abnormal placenta including growth disturbances, preeclampsia and preterm birth. Studies from murine models and chick embryo studies would suggest that placental structural and vascular changes contribute to congenital heart defects however, the involvement of placental abnormalities in congenital heart disease in humans, whether causal, commensurate or reactive, is under investigated. We aim to determine this relationship in humans and identify if this may provide a path for the potential treatment of CHD in utero.